2011
DOI: 10.1214/10-aap705
|View full text |Cite
|
Sign up to set email alerts
|

General notions of indexability for queueing control and asset management

Abstract: We develop appropriately generalized notions of indexability for problems of dynamic resource allocation where the resource concerned may be assigned more flexibility than is allowed, for example, in classical multi-armed bandits. Most especially we have in mind the allocation of a divisible resource (manpower, money, equipment) to a collection of objects (projects) requiring it in cases where its over-concentration would usually be far from optimal. The resulting project indices are functions of both a reso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…We have found that our analyses are more easily accomplished via optimisation problem (6) than via direct use of the Lagrangian relaxation (4). The use of c in place of W is well suited for proofs and calculations but, as we shall see, the equivalent problems formulated with variable W lend themselves much more directly to economic interpretation and heuristic understanding.…”
Section: Remarkmentioning
confidence: 99%
See 2 more Smart Citations
“…We have found that our analyses are more easily accomplished via optimisation problem (6) than via direct use of the Lagrangian relaxation (4). The use of c in place of W is well suited for proofs and calculations but, as we shall see, the equivalent problems formulated with variable W lend themselves much more directly to economic interpretation and heuristic understanding.…”
Section: Remarkmentioning
confidence: 99%
“…In order to construct strongly performing heuristics, we follow Whittle [18] and Glazebrook et al [4] in developing a Lagrangian relaxation of the original problem in which a charge is levied for the deployment of the key resource. In this relaxation the Lagrange multiplier (W ) has an economic interpretation as a charge for one unit of resource applied to production for one unit of time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors propose heuristic techniques for dealing with several classes of constraints that use the solutions for individual MDPs to construct an approximate global solution. Glazebrook et al (2011) consider the allocation of a divisible resource, such as manpower, money, or equipment, to a collection of tasks requiring it. The authors develop a notion of indexability for problems of dynamic resource allocation where the resource concerned may be assigned more flexibility than is allowed, for example, in classical multi-armed bandits.…”
Section: Related Workmentioning
confidence: 99%
“…Most recently, Glazebrook et al [15] have generalised the notion of indexability to a large class of resource allocation problems. We note, however, that the definition of indexability presented here does not arise out of a Lagrangian relaxation of an original problem involving only a running reward as is the case in [15]. Instead, in the context of a optimal stopping problems, indexability is a natural feature in the monotone comparative statics of parametrised families of forward problems.…”
Section: Monotonicity Of the Optimal Stopping Threshold In The Paramementioning
confidence: 99%